Reducing Gabaergic Inhibition Restores Cognitive Functions in a Mouse Model of Down Syndrome - Potier, Marie-Claude; Braudeau, Jerome; Dauphinot, Luce; Delatour, Benoit (CNS & Neurological Disorders - Drug Targets, 2014)
Alterations in excitatory-inhibitory balance occur in Down syndrome and could be responsible for cognitive deficits observed through the life of all individuals carrying an extra copy of chromosome 21. Excess of inhibition in the adult could produce synaptic plasticity deficits that may be a primary mechanism contributing to learning and memory impairments. In this study we discuss pharmacological treatments that could potentially alleviate neuronal inhibition and have been tested in a mouse model of Down syndrome. γ-aminobutyric acid (GABA) is the major inhibitory neurotransmitter in the mature central nervous system that binds to GABA-benzodiazepine receptors, opens a chloride channel and reduces neuronal excitability. These receptors have been extensively studied as targets for treatment of epilepsy, anxiety, sleep, cognitive disorders and the induction of sedation. Molecules that are either antagonists or inverse agonists of the GABA-benzodiazepine receptors are able to reduce inhibitory GABAergic transmission. However modulating the excitatory-inhibitory balance towards increase of cognition without inducing seizures remains difficult particularly when using GABA antagonists. In this study we review data from the literature obtained using inverse agonists selective for the α5-subunit containing receptor. Such inverse agonists, initially developed as cognitive enhancers for treatment of memory impairments, proved to be very efficient in reversing learning and memory deficits in a Down syndrome mouse model after acute treatment.
Keywords: down syndrome